PENGARUH DAN HUBUNGAN STRUKTUR ORGANISASI, BUDAYA ORGANISASI DAN SUMBER DAYA MANUSIA DENGAN KINERJA. Konteks: Bank Umum di Indonesia - Lasmaida Gultom; Musa Hubeis; M. Syamsul Maarif; Dadang Sukandar (University of Merdeka Malang, 2016)
AbstractResearch on the influence and relationship of organizational structures, organizational culture and HumanResources (HR) with performance of commercial banks in Indonesia has been done. The research objective is toanalyze the influence and correlation of organizational structure, organizational culture and human resourceswith performance of commercial banks in Indonesia by using multivariate regression and Spearman correlationto analize the data. The hypothesis was tested by using 84 respondents representing 84 commercial banksin Indonesia, which is obtained through online surveys with census sampling techniques. Results of multivariateregression and Spearman correlation show that organizational structure, organizational culture and HRhave a significant influence and relationship with performance of commercial banks in Indonesia.